Urianry Tract Calculi: A four years Expereince - Ahmad, Ijaz; Khattak, Abid Haleem; Khan, Nasrullah; Jan, Attaullah; Durrani, Sadia Nawaz (Journal of Postgraduate Medical Institute, 2011)
To study the pattern and management of urolithiasis. This retrospective observational study was carried out at surgical D unit of KTH, Peshawar from January 2001 to Decmeber 2004. Data of 852 patietns with urolithiasis, managed in the surgical unit in the four years period was evaluated information regarding age, sex, side site type of operation and chemical nature of the calculi was recorded on a proforma. Metabolic study was done in only selected cases. urolithiasis is a fairly common disease. commonest calculi found were calcium oxalate.